Analysis of student motivation in special soccer classes at high school - Imam Habib Abdillah; Prasetyo, Heru; Akhirta Putra; Listya Laksana Dewantara; Aptur Widitama Putra; Safa'at Arif Alan Romadhona; Dienda Lutfi Nur Aulia; Iqbal Muhammad Dzikrullah; Muhammad Zidan Alviko Putra; Deca Danu Qadafi; Hakim Akbar Baihaqi (Departement of Sports Coaching, Faculty of Sports Sciences, Universitas Negeri Yogyakarta, 2025)
This study aims to determine students' motivation in choosing the Special Sports Class (KKO) for soccer, the factors that influence it, and the differences in student motivation between State Senior High School 4 Yogyakarta and State Senior High School 1 Sewon Bantul in the 2022/2023 academic year. The research used a quantitative descriptive method with a survey approach. The research sample consisted of 60 soccer KKO students, comprising 30 students from SMA Negeri 4 Yogyakarta and 30 students from SMA Negeri 1 Sewon Bantul, selected using purposive sampling. Data collection was conducted through a questionnaire covering intrinsic and extrinsic factors, which had been tested for validity and reliability. Data analysis used descriptive statistics and difference tests (t-tests). The results showed that student motivation for choosing soccer KKO at SMA Negeri 4 Yogyakarta was in the moderate category, while at SMA Negeri 1 Sewon Bantul it was in the very high category. The motivation of students at SMA Negeri 4 Yogyakarta was more dominantly influenced by extrinsic factors, while the motivation of students at SMA Negeri 1 Sewon Bantul was more influenced by intrinsic factors. The difference test results showed that there was a significant difference in motivation between the two schools with a significance value of 0.000.